2021
DOI: 10.1186/s12941-020-00408-5
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of urine microbiota in obstructive urinary retention patients revealed by next-generation sequencing

Abstract: Background Urinary retention (UR) is a common urinary system disease can be caused by urinary tract obstruction with numerous reasons, however, the role of urine microbes in these disorders is still poorly understood. The aim of this study was to identify the urine microbial features of two common types of obstructive UR, caused by urinary stones or urinary tract tumors, with comparison to healthy controls. Methods Urine samples were collected from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…Likewise, they observed an increase in opportunistic pathogens such as Acinetobacter , Enterococcus , Comamonas and Delftia in patients with KSD and also an increase in Lactobacillus , which authors speculated was a self-protective response of the urobiota of these patients. Jiang et al [22 ▪ ] found, unlike these previous studies, an increase in Bacteroidetes in bladder urine microbiota of KSD patients, although Proteobacteria was the majority phylum. Likewise, increases in potential pathogens such as Pseudomonas , Proteus or Acinetobacter and decreases in Lactobacillus and Prevotella were observed.…”
Section: Urobiome and Kidney Stone Diseasecontrasting
confidence: 55%
See 1 more Smart Citation
“…Likewise, they observed an increase in opportunistic pathogens such as Acinetobacter , Enterococcus , Comamonas and Delftia in patients with KSD and also an increase in Lactobacillus , which authors speculated was a self-protective response of the urobiota of these patients. Jiang et al [22 ▪ ] found, unlike these previous studies, an increase in Bacteroidetes in bladder urine microbiota of KSD patients, although Proteobacteria was the majority phylum. Likewise, increases in potential pathogens such as Pseudomonas , Proteus or Acinetobacter and decreases in Lactobacillus and Prevotella were observed.…”
Section: Urobiome and Kidney Stone Diseasecontrasting
confidence: 55%
“…Infection was more conclusive in OA1 patients as they showed greater leukocyturia. Jiang et al [22 ▪ ], compared the bladder urine microbiota in patients with obstructive uropathy and healthy controls. Patients with obstructive uropathy had tumors or stones.…”
Section: Urobiome and Kidney Stone Diseasementioning
confidence: 99%
“…The bacteria discovered in this study, such as Sphingomonas , Propionibacterium , and Corynebacterium , have been reported in several previous studies on urinary microbiota ( Ahn et al, 2022 ; Cappelli et al, 2023 ; Nickel et al, 2022 ; Perovic et al, 2022 ; Popovic et al, 2018 ; Kim & Park, 2018 ). However, Methylophilus , identified in this study, has only been reported in earlier studies on human skin and gut microbiota ( Dekio et al, 2005 ; Jiang et al, 2021b ; Jiang et al, 2021b ; Lee et al, 2021 ; Zheng et al, 2023 ). It is necessary to conduct large-scale studies in the future to further clarify the bacterial composition in human urine, which will play a crucial role in redefining urinary tract infections.…”
Section: Discussionmentioning
confidence: 61%
“… 59 This genus is also overrepresented in the urine of humans with obstructive urinary retention secondary to both uroliths and uroepithelial tumors, and even has been directly isolated from nephroliths of humans. 65 , 66 The independent association of specific organisms with urolithiasis across species supports a potential role of core taxa, such as Acinetobacter , in disease pathogenesis. Acinetobacter secretes oxalic acid during experimental lecithin degradation and can contribute to mineralization of organic compounds in soil, but whether these properties translate into lithogenic risk in the urine remains unclear.…”
Section: Discussionmentioning
confidence: 95%